The Relationship between Spirituality and Meaning at Work and the Job Happiness and Psychological Well-Being: A Spiritual-Affective Approach to the Psychological Well-Being (International Journal of Management and Sustainability, 2014)
Health and well-being are such important issues for employees in the workplace. Given the importance of this issue, this study was conducted to investigate the role of spirituality and meaning at work for job happiness and psychological well-being. The research design used in this study was correlation one and the sample consisted of 204 numbers of revenue & customs staff of Isfahan and Tehran cities. The research questionnaires were spirituality and meaning at work questionnaires, job happiness scale and psychological well-being questionnaire.¬ The research hypotheses were analyzed by Pearson correlation coefficient and structural equation modeling. The results showed that there is a positive and significant relationship between spirituality and meaning at work and job happiness and psychological well-being. The results of structural equation modeling also showed that during a series of chain relationships first spirituality and meaning at work communicate with job happiness and psychological well-being and then job happiness reinforces psychological well-being. Totally, the results of this study showed that psychological well-being at work can be considered as a variable with spiritual/affective basis in the workplaces.